Understanding business time-to-event problems using survival data mining - Linoff, Gordon S. (Henry Stewart Talks, 2008)
Background on survival analysis from a data miner's perspective, Introduction to key ideas in survival analysis: hazards, survival, competing risks, Understanding survival and hazard charts, Quantifying loyalty marketing program, Voluntary and involuntary churn, Forecasting
Archived at 2022/03/17